Advancing the study of parental involvement to optimise the psychosocial development and experiences of young athletes - Harwood, C. G.; Knight, C. J.; Thrower, S. N.; Berrow, S. R. (Psychology of Sport and Exercise, 2019)
The purpose of this article is to review and critique the literature in youth sport that specifically relates to parental influence on the experiences and psychosocial development of young athletes. First, we consider the literature examining the extent to which parental involvement in organised youth sport has been associated with psychosocial outcomes in young people. Within this critique, we draw upon what has been learned from the sport-based positive youth development (PYD) and life skills literature. Second, we address conceptual and methodological limitations of existing literature (e.g., homogeneity of samples, oversimplification of parenting in sport, studying parental involvement in isolation) and target key scientific gaps that exist in facilitating our understanding of optimal parental involvement (e.g., raising parental awareness and facilitating opportunities to support psychosocial development, improving coach education to facilitate parent-coach relationships, collaborating with coaches through well designed interventions, working on the "right" assets at the right time). Such gaps represent how parents appear to have been overlooked within the intentional process of psychosocial development. We offer concluding remarks about the future of youth sport in this area and provide specific recommendations to inspire future researchers and practitioners towards the challenge of empowering parents and more fully enabling their potential.